Effect of formulation variables on rheology, texture, colour, and acceptability of apple jelly: modelling and optimization - Garrido, Juan Ignacio (2015)
The objective was to study and model the effect of the main formulation variables on the rheological and mechanical properties, colour and overall acceptability of apple jelly, and to optimize formulation variables in order to maximize overall acceptability. Formulation variables were juice proportion in the initial juice-sugar mix (J: 350–550 g/kg), product pH (2.8–3.6), concentration of added pectin (P: 0–10 g/kg), and final content of soluble solids (SS: 625–725 g/kg). Anova results showed that P was the main effect on all the rheological and mechanical properties. The strength of the pectin gel network increased at increasing values of P. Consequently, the jellies were more elastic and firm but more brittle, as well as more adhesive. Also, more work was required to disintegrate the jellies. Besides P, also J had a significant positive effect on storage modulus and adhesiveness, while SS had a significant positive effect on cohesiveness. Colour parameters were mainly affected by J. Overall acceptability was significantly affected by J > pH > SS, while P had no significant effect. The optimum was calculated to be at J = 500 g/kg, SS = 700 g/kg, pH = 3.4, and P = 5 g/kg.